Evaluation of clinical pharmacy services in the intensive care unit of a Tertiary University Hospital in the Northwest of Iran - Ata Mahmoodpoor; Arman Kalami; Kamran Shadvar; Taher Entezari-Maleki; Hadi Hamishehkar (Journal of Research in Pharmacy Practice, 2018)
Objective: Current literature indicates that the presence of clinical pharmacists in hospitals results in improved patient care, rational drug therapy, and treatment costs. This study assessed the clinical pharmacy services in the intensive care unit (ICU) of a tertiary hospital at Tabriz University of Medical Sciences, Iran. Methods: During a 9-month cross-sectional study (2014–2015), the clinical pharmacy interventions in 27 sessions and educational activities for patients and health-care professionals were randomly assessed based on the Australian guideline and standard of practice for clinical pharmacy. The interventions of clinical pharmacist were evaluated in terms of their clinical importance. Findings: In this study, a total of 832 interventions on 242 patients were performed by the clinical pharmacist, and approximately 93.6% of the interventions were approved by the attending physician. Most interventions concerned adding a new medication to a drug regimen or switching to a needed new medication. Each patient received an average of three interventions. The clinical pharmacist provided drug information to employees and medical staff in 108 of the total 832 interventions (13%). Medical residents who were surveyed indicated that the quality of education, research, and patient care was improved by the attendance of a clinical pharmacist. Conclusion: The results of this study show that the collaboration of a clinical pharmacist with the medical staff of an ICU can improve pharmacotherapy approach and increase the quality of education.